Effectiveness of the ICARE-Modification Model in Training Students’ Critical Thinking Skills - Rita Makdalena; Rudiana Agustini; Raharjo Raharjo (IKIP Widya Darma Surabaya, 2026)
Objective: Developing students’ critical thinking skills remains a central challenge in higher education, particularly in teacher education programs that demand higher-order cognitive competencies. This study investigates the effectiveness of the ICARE-Modification model—an extended instructional framework integrating Introduction, Connection, Application-modification, Reflection, and Extension stages with AI problem-solving activities—in enhancing undergraduate students’ critical thinking skills. Method: A quasi-experimental design with a non-equivalent control group was employed involving 60 undergraduate students enrolled in a teacher education program. The experimental group received instruction using the ICARE-Modification model, while the control group experienced conventional lecture-based learning. Data were collected through a validated open-ended critical thinking test assessed using an analytical rubric covering questioning, analysis, evaluation, logical reasoning, and solution formulation. Data were analyzed using independent samples t-tests and Cohen’s d effect size. Results: The findings suggest that the ICARE-Modification model creates a more interactive and cognitively engaging learning environment that supports the development of students’ critical thinking skills. Through structured stages of learning that involve exploration, discussion, and reflection, students are encouraged to actively construct knowledge and evaluate their own reasoning processes, which ultimately leads to better learning outcomes in critical thinking. Novelty: This study introduces the ICARE-Modification model, an extended instructional framework that integrates the traditional ICARE stages with AI-assisted problem-solving activities to foster students’ critical thinking skills in teacher education. Unlike previous studies that apply ICARE as a conventional instructional model, this research incorporates structured cognitive scaffolding and AI-supported reflective learning to enhance higher-order thinking processes.